Effects of Tamarindus indica (Linnaeus 1753) pulp-fortified diets on the gut microflora and morphometry in African catfish Clarias gariepinus (Burchell 1822) - Olarinke Victoria Adeniyi; Flora Eyibio Olaifa; Benjamin Obukowho Emikpe; Samuel Temitope Ogunbanwo (Aceh Journal of Animal Science, 2021)
The global criticism on the adverse effects of synthetic antibiotics including destabilization of gut microflora necessitated research into natural alternative like phytobiotics. Tamarind pulp is a phytobiotic known for its antimicrobial, growth-promoting and antioxidants properties, with little information on the mechanism of its growth promotion in fish. Therefore, this study investigated the effects of tamarind pulp (TP) meal as feed additives on the growth, gut microflora, and morphometry in Clarias gariepinus. The fish were fed with diets fortified with graded levels (0.0%, 0.5%, 1.0%, 1.5% or 2.0%) of TP or 0.2% oxytetracycline (OTC). Fish weight gain, feed conversion ratio (FCR), gut microflora and morphometry were determined. The weight gain of fish rose (P 0.05) with increasing levels of TP, while the FCR reduced significantly, compared to those fed the control diets. The total viable counts and enterobacteriaceae from the gut of fish fed OTC-fortified control diet was lower, compared the fish fed unfortified control (0.0% TP) diet and diets containing TP. Fish fed 1.0-2.0% TP-fortified diets had significantly higher yeast counts, compared to those fed other diets, while on the other hand higher (P0.05) Streptococcus sp was obtained from fish fed the control diets. The thickness of muscular lining of the base of villi, villi height and absorption area were higher (P ˂ 0.05) in fish fed OTC-fortified (C2) diet, compared to other treatments, while lower crypt depth were obtained in fish fed TP-fortified diets. The correlation analyses showed moderate negative (R = -0.539 at P 0.05) relationship between FCR and population of enterobacteriaceae while a very strong positive relationship (R = 0.848 at P 0.01) existed between FCR and population of haemolytic Streptococcus. The enhanced growth in fish fed TP-fortified diets could be accredited to the reduced crypt depth and colonization of yeast and reduced Streptococcus counts. Therefore the application of tamarind pulp meal at 2% is recommended for enhanced growth and healthy gut microflora composition.